International Economic Relations and the Development Possibilities of Peru - Herska, Claudio (1981)
Some events in the frame of economic international relations that affect the options of Peru in its development strategy of the 80s are discussed here. The article deals with these subjects: basic products, manufacture exports, treatment of foreign capitals and some initial appreciations with respect to the events in the field of long term capital flows.